Digital Transformation in Street Food Business in Malang: AI Application Training for Content Creation and Effective Promotion Strategies - Yogatama, Ahmad Nizar; Sidi, Agus Purnomo; Anjaningrum, Widiya Dewi; Bukhori, Muhammad; Dura, Justita; Cahyaningtyas, Fadilla; Andriany, Lussia Mariesti; Hanif, Rifki (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study investigates the integration of Artificial Intelligence (AI) in digital marketing for street food businesses in Malang, focusing on training housewives to improve content creation and promotion strategies. The research aims to bridge the digital gap for small-scale food vendors by providing essential digital skills and AI tools. Method: The research employed a mixed-method approach, including pre-training assessments, online training sessions, and personalized mentoring. A total of 20 housewives running street food businesses participated in the training, which was conducted over three months. The AI tools used included Canva AI and Flair AI for photo editing, content creation, and social media optimization. Practical Applications: The study demonstrates how AI-driven tools can enhance social media engagement, brand visibility, and customer interaction for street food vendors. This initiative provides a model for empowering small business owners to leverage digital marketing tools effectively, contributing to their long-term success. Conclusion: The training resulted in significant improvements in participants' digital marketing capabilities, with increased confidence in using AI tools. The findings highlight the transformative potential of AI for MSMEs, particularly in enhancing the competitive edge of street food businesses in Malang.